Recombinant production of a hybrid plasminogen activator composed of surfactant protein B and low-molecular-weight urokinase - Ruppert, Clemens; Mahavadi, Poornima; Wygrecka, Malgorzata; Weaver, Timothy E.; Magdolen, Viktor; Idell, Steven; Preissner, Klaus T.; Seeger, Werner; Günther, Andreas; Markart, Philipp (Thrombosis and Haemostasis, 2008)
Intraalveolar fibrin deposition is commonly observed during acute inflammatory and chronic interstitial lung diseases and may contribute to impairment of surfactant function and gas exchange.We recently described a chemically cross-linked chimeric protein consisting of surfactant protein (SP)-B and urokinase (uPA) for targeting alveolar fibrin under conditions such as acute respiratory distress syndrome (ARDS) or lung fibrosis.We now investigated the feasibility of a recombinant production of a fusion protein encoding mature SP-B and uPA, termed SPUC. Four different SPUC proteins (N-term SP-B/C-term uPA, N-term uPA/C-term SP-B, each +/− His-tag) were prepared by cloning the cDNA encoding mature SP-B and low-molecular-weight uPA into the expression vector pcDNA3.1. CHO-cells were transfected with the constructs and the supernatant and cell lysates were analyzed for expression of SPUC.Using a chromogenic substrate assay uPA activity was found in supernatants and lysates of transfected cells with highest activities related to the N-term uPA/C-term SP-B (+/− His-tag) construct in supernatants 48h after transfection.Casein enzymography showed an enzymatically active fusion proteins with a molecular weight of ∼ 42 kDa in the supernatant of cells transfected with the N-term uPA/C-term SP-B (+/− His-tag) construct,but only a minor activity with the N-term SP-B/C-term uPA construct. The N-term uPA/C-term SP-B construct was also shown to possess higher resistance towards inhibition by plasminogen activator inhibitor-1.We conclude that recombinant production of a fusion protein consisting of mature SP-B and uPA is feasible, when the SP-B moiety is fused to the C-terminus of urokinase.
Keywords: Urokinase; pulmonary surfactant; acute lung injury; fusion protein